Pendampingan Literasi Digital pada UMKM melalui Pendekatan Coaching Clinic di Desa Sukasirnarasa, Kecamatan Rancakalong - Sobari; Bintang Prima Arya Mahesa; Silvia Aprianti; Viera Ayu Kirana; Mohammad Raffy Pradipta Putra; Rafa Mut Mainah Ibni Imam; Meli Mulyawati; Neneng Rizqoh; Iwan Satriyo Nugroho (Politeknik Piksi Ganesha Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a vital role in the national economy, but face increasingly complex competition in the digital era. Many MSMEs face challenges in adopting technology, requiring increased digital literacy to survive and compete. This study aims to apply a digital literacy strengthening model to MSMEs in Sukasirnarasa Village through a coaching clinic approach. Using a descriptive qualitative method, data was collected through observation and in-depth interviews involving MSMEs to explore their understanding and needs related to the use of technology. The results of the study indicate that the coaching clinic approach is effectively implemented to improve digital literacy. This model is successful because it emphasizes active participant participation, communication, and collaboration, and includes the development of individual competencies such as technical skills, critical understanding, and communication skills in a digital context. This study contributes in the form of a practical coaching model that can be adopted to improve the capacity and competitiveness of MSMEs in facing the challenges of the digital era.